Documentation of Medicinally Important Plants from the Landslide Prone Areas of East Sikkim, India: A Survey Report - B. C. Basistha4, M. L. Arrawatia4, L. Lepcha1*, S. Guha Roy2, A. Sarkar3, (Journal of Phytology, 2011)
In the present study, field survey for exploring the medicinal plant biodiversity were conducted in the landslide prone areas of East Sikkim, India.Ã‚Â Twenty five medicinally important plants were collected and identified from four distinct study areas. The comparative study has analyzed that the landslide eruptions are playing major role in scaling these medicinal plant species towards vulnerability. The present study has come Ã‚Â Ã‚Â Ã‚Â Ã‚Â up with species frequency status which helps to predict the present existing status of medicinal plant species which suggests adopting a serious concern in conserving these valuable species in the state before their extinction. The common medicinal species like Artemesia indica, Osbekia nepalensis, Potentella fruticosa, Polygonum molle are found to be under tremendous threat. The study also found some of the species already been Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â extinct from landslide areas which have earlier occupied the region abundantly. The study shall play a major role for the researchers in monitoring the values and importance of species inhabiting such vulnerable locations and help to approach efficient mitigative measures in conserving these plant species.